Technology-Mediated Relationship Maintenance in Romantic Long-Distance Relationships: An Autoethnographical Research through Design. (3rd May 2020) - Chien, Wei-Chi; Hassenzahl, Marc
Abstract : Many routine relationship maintenance activities, such as supporting each other in the household, rely on responsive interaction. Unfortunately, the physical separation typical for long-distance relationships severely limits the opportunities to support each other in everyday life. This paper reports an autoethnographical research through design of this, in human–computer interaction (HCI) still quite uncharted, territory. In over two years of design research, the first author developed four concepts, materialized them as functional artifacts, and used them extensively with Claire, his partner. His designerly journey into alternative practices for Claire and him revealed the complexities and intricacies of designing "couple technologies" for the real world. For instance, it highlighted the importance of going beyond mere abstracted presence toward enabling meaningful everyday responsive interaction. We found that such meaningful interaction can be created by focusing on possible practices of mutual caring. Besides providing valuable insights for designers of technology-mediated relatedness, we discuss autoethnographical research through design as a mode of knowledge production in the context of HCI.